Perancangan Jig Positioner pada Proses Pengelasan Tip Coaming Trailer SST74 - Eko Ari Wibowo (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
SST 74 trailer is one of the transportations used to transport materials in mining areas. In the trailer there is a coaming component that functions as a retaining frame so as not to deform and as an addition to the load capacity of the trailer. The purpose of this study is to design a tool to accelerate the transfer of coaming before welding is processed. The French method is used to identify problems that occur in the field and determine the jig positioner design concept, while the Finite Element Analysis method is used to validate the design. The results of the design are used as the basis for the manufacturing process of the tool. The projected reduction in estimation for the process of moving the coaming component which was previously 99 minutes to 35 minutes with the assumption that the jig positioner rotation is 1 rpm. A cost efficiency of 64% or Rp. 66,150,000 is projected if the coaming jig positioner is realized on the SST74 Trailer.